Examining current best-practices for the use of wild post-larvae capture, culture, and release for fisheries enhancement - Richardson, Laura E.; Lenfant, Philippe; Clarke, Leo J.; Fontcuberta, Amelie; Gudefin, Anaïs; Lecaillon, Gilles; Le Vay, Lewis; Radford, Andrew N.; Simpson, Stephen D. (Frontiers in Marine Science, 2023)
Demand for marine fisheries is rising despite global impacts on the productive capacity of wild fish stocks due to overfishing, habitat loss, and global warming. Fisheries enhancement programs—aimed at augmenting stocks by releasing juveniles into the wild—are expected to play an increasingly important auxiliary role in addressing capture-based fishery limitations into the future. However, concerns exist over the impacts and efficacy of aquaculture-based enhancement (ABE), releasing captive-bred fish into wild populations. An alternative but understudied approach for fisheries enhancement is wild post-larvae capture, culture, and release (PCCR). Here, we provide an overview of the PCCR process, from initial planning to measuring success, providing an overview of its implementation in a viable finfish fishery, the white seabream Diplodus sargus in the Mediterranean. We discuss management application of PCCR-based enhancement and its limitations, highlighting existing knowledge gaps and future research required to realize the full potential of this alternative approach. Notwithstanding some limitations–including limited uptake for full evaluation, some species restrictions, density-dependent mortality, and the remaining open challenge for stock enhancement generally of tracking released fish through to reproduction–PCCR offers potential as a credible auxiliary management tool for fisheries restoration.